Extent of formal use of Iban among the Iban community in Sarawak. - Lilly, Metom; Ting, Su Hie (2023)
The study examined the extent of formal use of Iban among the Iban community. Questionnaire data from 1,204 Iban respondents showed that mastery of Iban is through informal language acquisition rather than formal learning. Only 28% of the respondents attended kindergartens using Iban as the medium of instruction and 33.1% attended meetings conducted in Iban. Altogether 93.8% of the respondents could speak Iban fluently, regardless of whether they were living among Ibans. A higher percentage of Iban respondents in Iban-dominant areas could read and write in Iban, compared to those in non-Iban dominant areas. Over 70% of the Iban respondents reported that they had read printed materials in Iban. More Iban respondents owned Iban textbooks and grammar books (56%) and Iban story books (52%) than Iban dictionaries (40%). The findings suggested low confidence in the potential status of Iban as an official language due to inadequate written materials in Iban.